2001
DOI: 10.1017/s0022112001004633
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of boundary-layer separation and transition at a change of surface curvature

Abstract: Transition arising from a separated region of flow is quite common and plays an important role in engineering. It is difficult to predict using conventional models and the transition mechanism is still not fully understood. We report the results of a numerical simulation to study the physics of separated boundary-layer transition induced by a change of curvature of the surface. The geometry is a flat plate with a semicircular leading edge. The Reynolds number based on the uniform inlet velocity and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
129
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 255 publications
(172 citation statements)
references
References 33 publications
(79 reference statements)
36
129
1
1
Order By: Relevance
“…V) resulting in the flapping. Note that the findings of Yang and Voke 43 and Deck and Thorigny 42 suggest that the cause of shear-layer flapping is due to convective instabilities in the shear layer.…”
Section: Vortex Shedding and Shear-layer Connectionmentioning
confidence: 96%
“…V) resulting in the flapping. Note that the findings of Yang and Voke 43 and Deck and Thorigny 42 suggest that the cause of shear-layer flapping is due to convective instabilities in the shear layer.…”
Section: Vortex Shedding and Shear-layer Connectionmentioning
confidence: 96%
“…(10), which are expensive to compute and store and increase significantly the requirements for smoothness of the computational mesh as they involve second order derivatives of the metrics of the geometric transformation. FT-1 formulations have been proposed and applied to solve the incompressible Navier-Stokes equations, see for example [17,18], but because of the aforementioned difficulties such methods have not been widely used in the literature.…”
Section: Overview Of Staggered Grid Formulations In Curvilinear Coordmentioning
confidence: 99%
“…The volume fluxes are obtained by discretizing and solving their respective transport equations, which, for reasons that will soon become apparent, are formulated as follows: (16) where ℜ q (q = 1, 2, 3) denote the contravariant fluxes of the convective and viscous terms: (17) The key difference between the proposed method and the FT-2 approach is that the ℜ q terms at their respective surface centers are not obtained by discretizing the C and D terms at the surface centers (as required in approach FT-2 as shown in Eq. (14)) but are reconstructed by interpolation from the volume centers.…”
Section: Hybrid Staggered/non-staggered Approach In Curvilinear Coordmentioning
confidence: 99%
“…Further numerical and experimental analyses by Yang and Voke (2001), Lang et al (2003) showed that transition is the result of amplification of K-H instabilities in the separated shear layer, which leads to the roll-up and subsequent shedding of large vortices at the rear part of the bubble. These results are supported by recent studies from, e.g.…”
Section: Introductionmentioning
confidence: 99%